Potensi polisakarida dari limbah buah-buahan sebagai koagulan alami dalam pengolahan air dan limbah cair: Review - Hans Kristianto; Angelica Jennifer; Asaf Kleopas Sugih; Susiana Prasetyo (Jurnal Rekayasa Proses, 2020)
Nowadays, various studies related to utilization of biobased materials as natural coagulants have been explored. Based on the source, natural coagulants can be classified as animal, vegetable, or microbial based. Furthermore, based on the active ingredients, it can be classified as protein, polyphenols, and polysaccharides. Polysaccharides are abundant natural ingredients and are often found in plants or animals. In this study, we focused on polysaccharides, especially those from fruit waste, such as seeds and fruit peels. It is known that around 25-30% of the total weight of fruit is generally wasted, even though it contains phytochemicals and various active ingredients that can be utilized, especially as a natural coagulant. This review will focus on the use of pectin and starch from fruit waste as natural coagulants for water- wastewater treatment. Generally, pectin is commonly found in the skin of fruits as part of the cell wall structure, while starch is found in fruit seeds as food reserves. To be used as a natural coagulant, pectin or starch need to be extracted first. In particular, starch needs to be modified either physically or chemically. The coagulation mechanism of pectin and starch usually follows the interparticle bridging mechanism. The use of pectin and starch from fruit waste needs to be explored and further investigated, to substitute the use of chemical coagulants.